“Endangered or an artifact of unsound taxonomy? Case of the critically endangered bush frog Philautus sanctisilvaticus Das and Chanda, 1997” - Mirza, Zeeshan A.; Warekar, Priya; Mohapatra, Pratyush P.; Raju, David; Patil, Pranad; Dutta, Sushil K.; Pal, Saunak (Zootaxa, 2019)
We investigated the phylogenetic relationship of the Critically Endangered bush frog Philautus sanctisilvaticus Das and Chanda, 1997 and other species distributed across the fragmented forests of Deccan Peninsula and the northern Eastern Ghats. A short fragment of the mitochondrial 16S rRNA gene was employed to assess phylogenetic relationships across Philautus sanctisilvaticus Das and Chanda, 1997, Raorchestes terebrans (Das and Chanda, 1998) and Philautus similipalensis Dutta, 2003. All sequenced specimens, including material from near the type localities of P. sanctisilvaticus (Amarkantak) and P. similipalensis (Simlipal) were genetically extremely similar, with pairwise uncorrected distances <1% in the 16S gene, and were phylogenetically placed within the genus Raorchestes. The results based on morphology are ambiguous and do not go hand in hand with molecular data, which however do not provide support for a three species hypothesis either. our findings advocate the need for making nomenclatural amendments. Philautus sanctisilvaticus Das and Chanda, 1997, is the first available nomen for this taxon, and we propose to include this species in Raorchestes as Raorchestes sanctisilvaticus (Das and Chanda, 1997), and to consider the nomina Philautus terebrans Das and Chanda, 1998 syn. nov. and Philautus similipalensis Dutta, 2003 syn. nov. as junior subjective synonyms for this nomen following the Principle of Priority in article 23.1 of the ICZN. The findings are notable from the point of conservation of the species and present a novel case with remarkable genetic homogeneity across the fragmented forests of Deccan Peninsula and Eastern Ghats.